177Lu-DOTATATE Peptide Receptor Radionuclide Therapy: Indigenously Developed Freeze Dried Cold Kit and Biological Response in In-Vitro and In-Vivo Models. Issue 1 (11th February 2021) - Roohi, Samina; Rizvi, Shakera Khatoon; Naqvi, Syed Ali Raza
Somatostatin receptors (SStR) based 177 Lu-DOTATATE therapy is known as one of the highly effective neuroendocrine tumors (NETs) treatment strategy. Development of DOTATATE freeze-dried kit for imaging and therapy of SStR positive NETs is a prime goal in neuroendocrine cancer research. The present work describes the development of 177 Lu-DOTATATE freeze dried cold kit for indigenous needs, through technology development fund (TDF) program offered by Higher Education Commission (HEC) Pakistan. The parameters for freeze dried kit production was optimized and tested the stored lyophilized cold kits for different time intervals after labeling with 177 Lu radioisotope. The effect of ligand to radionuclide ratio, pH and reaction time at 90°C was recorded. Five times greater molar concentration of ligand, pH 5 and 30 min reaction time were the effective reaction conditions for maximum radiochemical yield. The radiolabeling yield at 1 day, 1-week and 4-week post storing period showed ∼100% radiochemical yield. The biodistribution study using rat model depicted the absence of non-targeted accumulation while glomerular filtration rate also explains the rapid renal washout. Cytotoxicity study showed quite favorable results for subjecting the radiopharmaceutical to clinical practice in Pakistan.